PENINGKATAN KUALITAS PENDIDIKAN MELALUI KEGIATAN BIMBINGAN BELAJAR GRATIS DI DESA SAMPALI Kec. PERCUT SEI TUAN - Sindi Atikah; Hafizah Luthfiyyah NurJihan; Nelly Orita Imelda; M. Rizaldy Wibowo; Rudyansyah R. Simarmata (Cattleya Darmaya Fortuna, 2022)
This study uses the method of socialization, the technique used in the socialization is door to door. So we visited the residences of several parents of children who are elementary school students to provide information that we would implement a Free Learning program which aims to help parents assist their children in studying at home. Using the Free Learning implementation method, this phase includes a minimum of 5 students and a maximum of 13 students from different classes who join our program. Results Community service activities in Sampali Village, Percut Sei Tuan District, Deli Serdang Regency began with a survey conducted by ourselves on September 15, 2021. The results of the activities carried out are as follows: Overcoming problems so that children want to take part in this program, With methods that are easier to understand, Flexible learning methods do not force children and they like to learn while playing, Parents and their children easily understand learning methods implemented, the community helped us in finding local children to join the Free Learning program, the parents were very grateful to us for our presence.